Business ecology: A new science - H. G. Clarke (South African Journal of Business Management, 1983)
This paper is a theoretical exposé of the relatively new field of business ecology.It presents a conceptual model of how the organization interacts with the environment. Although the concepts are well established in ecology, the author demonstrates their business application.
Keywords: 650